A randomized controlled trial of a homeopathic syrup in the treatment of cold symptoms in young children. (December 2016) - Jacobs, Jennifer; Taylor, James A.
Highlights: OTC cold medications in preschool children have not been found to be effective. Children ages 2–5 with colds were treated with a homeopathic syrup or a placebo. Those given homeopathy had a significant decrease in symptoms after 24–48 h. Abstract: Background: There is little evidence that the decongestant, antihistamine, or cough suppressant medications commonly used to treat cold symptoms in preschool children are effective. One option for treating cold symptoms in young children is with homeopathy. This study was conducted to determine if a homeopathic syrup was effective in treating cold symptoms in preschool children. Methods: Children 2–5 years old diagnosed with an upper respiratory tract infection were randomized to receive a commercial homeopathic cold syrup or placebo. Parents administered the study medication as needed for 3 days. The primary outcome was change in symptoms one hour after each dose. Parents also assessed the severity of each of the symptoms of runny nose, cough, congestion and sneezing at baseline and twice daily for 3 days, using a 4-point rating scale. A composite cold score was calculated by combining the values for each of the four symptoms. Results: Among 261 eligible participants, data on 957 doses of study medication in 154 children were analyzed. There was no significant difference in improvement one hour after the dose for any symptom between the two groups. Analysis of twice daily data on the severity of cold symptoms compared to baseline values found that improvements in sneezing, cough and the composite cold score were significantly greater at both the first and second assessments among those receiving the cold syrup compared to placebo recipients. Conclusion: The homeopathic syrup appeared to be effective in reducing the severity of cold symptoms in the first day after beginning treatment.